Beyond Technology: Strategies for Managing Digital Transformation in Traditional Sectors - Zulfikri, Agung; Prayitno, Hadi; Yuda, Fardan Zeda Achmadi (Novatio : Journal of Management Technology and Innovation, 2024)
Digital transformation has become a defining force in reshaping traditional industries, yet its successful implementation requires navigating complex technological, organizational, economic, and regulatory challenges. This study presents a narrative review aimed at synthesizing existing literature on change management strategies in digital transformation across sectors such as manufacturing, healthcare, agriculture, and energy. Literature was collected through databases including Scopus, Web of Science, PubMed, and Google Scholar, using targeted keywords such as digital transformation, traditional industries, change management strategies, Industry 4.0, and sustainability. The review analyzed empirical studies, case studies, and theoretical contributions published between 2015 and 2025. Findings reveal that technologies like artificial intelligence, Internet of Things, blockchain, and digital twin systems enhance operational efficiency and sustainability but face barriers related to resource constraints, cultural resistance, and fragmented regulatory frameworks. Organizational factors, particularly leadership vision and employee skills development, emerge as central to overcoming resistance and enabling adoption. Economic disparities between large firms and SMEs remain a significant challenge, while supportive public policies and international regulatory harmonization play critical roles in facilitating progress. The discussion highlights systemic social, economic, and political influences on digital adoption and underscores the importance of continuous training, public-private partnerships, and adaptive policies as strategies to address persistent challenges. The study concludes that digital transformation is both a technological and socio-economic imperative, requiring coordinated strategies and context-sensitive approaches to achieve sustainable and inclusive outcomes.